Ethyl 1-benzoyl-4-hydroxy-2,6-diphenyl-1,2,5,6-tetrahydropyridine-3-carboxylate - Aridoss, G. (International Union of Crystallography, 2011)
In the title compound, C(27)H(25)NO(4), the tetrahydropyridine ring adopts a half-chair conformation. The three phenyl rings form dihedral angles of 66.33 (7), 87.36 (8) and 36.90 (7)° with the least-squares plane through the tetrahydropyridine ring. The molecular conformation is stabilized by an intramolecular O—H⋯O hydrogen bond, generating an S(6) motif.